Impact of the International Tumor Budding Consensus Conference Recommendations in Oral Cancer - Kopecka, Katerina; Herman, Michal; Michalek, Jaroslav; Zapletalova, Jana; Hermanova, Marketa; Liptakova, Priska; Hendrych, Michal; Mozola, Michal; Pink, Richard (Oral diseases, 2025)
OBJECTIVES: Tumor budding was suggested as a valuable prognostic factor in oral squamous cell carcinoma (OSCC) but lacks a standardized scoring system. This study evaluates tumor budding in OSCC using the scoring system recommended by the International Tumor Budding Consensus Conference (ITBCC) 2016. MATERIALS AND METHODS: The study included 114 patients with resected OSCC. Tumor budding was evaluated according to ITBCC criteria and assigned to three categories (low, intermediate, and high tumor budding). The associations between tumor budding and clinicopathological parameters were examined and survival rate analyses were performed by the Kaplan-Meier method. The prognostic value of tumor budding was assessed by Cox regression analysis. RESULTS: Significant correlations of tumor budding with clinicopathological parameters including lymph node metastasis, grade, stage, perineural and lymphovascular invasion, and local recurrence were found. Intermediate and high tumor budding were significantly and independently associated with worse disease-free survival. High tumor budding was identified as an independent prognostic factor for disease-specific and overall survival. CONCLUSIONS: The ITBCC scoring system represents a simple, feasible, and reproducible method to evaluate tumor budding in OSCC. Tumor budding, according to ITBCC criteria, showed its prognostic value in resected OSCC, and its incorporation into the histopathological reporting guidelines should be considered.
Keywords: Humans; lidé středního věku; Female; Aged; dospělí; Neoplasm Invasiveness; senioři; lidé; Lymphatic Metastasis; přežití bez známek nemoci; nádory úst; lymfatické metastázy; tumor budding; Adult; staging nádorů; ženské pohlaví; Male; Middle Aged; oral squamous cell carcinoma; prognóza; Mouth Neoplasms; Aged, 80 and over; Disease-Free Survival; senioři nad 80 let; spinocelulární karcinom; invazivní růst nádoru; Carcinoma, Squamous Cell; lokální recidiva nádoru; Neoplasm Staging; míra přežití; histopathology; mužské pohlaví; prognosis; Neoplasm Recurrence, Local; Prognosis; Survival Rate